018 The national audit of seizure management in hospitals: round 3 (NASH 3). Issue 6 (27th May 2022) - Powell, Graham; Taylor, Claire; Dixon, Pete; Pearson, Mike; Tudur-Smith, Catrin; Marson, Tony
Abstract : Introduction: Seizures are a common presentation in the Emergency Department (ED). Previous rounds of NASH (2011 and 2013) identified major deficiencies in the provision of care and a disconnection between acute medicine and neurology services. Has there been any improvement? Methods: Setting: 137 Hospital sites across the UK. Participants: 4132 attendances between 01/06/2018 – 30/06/2019 were assessed, 61% had a prior diagnosis of epilepsy and 23% presented with suspected first seizure. Outcome Measures: Data were recorded to assess prior care, the acute presentation and subsequent care including referral for specialist review. Results: For patients presenting with first seizure an attempt was made to contact an eyewitness in 70.4%. CT Brain was requested in the ED in 66%, which has increased from 45% in NASH 1. Onward referral for specialist review was requested in 64%. For patients with epilepsy 55% had not seen an epilepsy specialist in the previous 12 months. CT Brain was requested in 30%, increasing from 17% in NASH 1. Specialist review was requested for 35% who had not seen a specialist in the previous 12 months and for 44% who had. Conclusions: There has been little improvement in the past decade. Improvements are urgently needed to improve the wellbeing of patients presenting with seizures, patients with epilepsy and the efficiency of the healthcare system. gpowell@liv.ac.uk 34